Armenia Economic Update, Spring 2015 : Accelerating Reforms, Increased Uncertainty - World Bank Group (World Bank, Washington, DC, 2015)
Armenias economic growth remained resilient in 2014. Output expansion slowed to 3.4 percent in 2014, relative to 3.5 percent in the previous year. On the supply side, while services particularly transport and telecoms), agriculture, and manufacturing performed well, construction, mining, and energy made negative contributions to output growth. On the demand side, net exports were the main contributor to growth, offsetting weak private consumption and negative private investment. However, by the last quarter, Russias economic slowdown and the steep depreciation of the ruble began to depress remittances, FDI inflows, and exports. Few jobs were created during the year, and the unemployment rate reached to 17.6 percent in 2014. A weak labor market, combined with slower emigration and return migration from Russia, are likely to have undermined growth in the incomes of the poor. Declining remittances and higher inflation in the last few months of 2014 reinforced these trends. Poverty at US$2.5/day was 30.2 percent in 2014, still above the levels recorded in the period leading up to the 2008 financial crisis. Fiscal policy continued to be prudent throughout the year, and monetary tightening responded to the currency depreciation. Developments in Russia will adversely affect economic growth in 2015, underscoring the needfor Armenia to press ahead with structural reforms.